Mortality and progeny production of four stored-product insect species on three grain commodities treated with Beauveria bassiana and diatomaceous earths. (September 2021) - Wakil, Waqas; Schmitt, Thomas; Kavallieratos, Nickolas G.
Abstract: Laboratory bioassays were conducted to estimate the effectiveness of the entomopathogenic fungus Beauveria bassiana (Bals.-Criv.) Vuill. (Hypocreales: Cordycipitaceae) at 1.5 × 10 8 and 1.5 × 10 10 conidia/kg grain alone or mixed with the diatomaceous earths (DEs) Protect-It at 150 ppm and DEBBM at 50 ppm against adults of the rusty grain beetle, Cryptolestes ferrugineus Stephens (Coleoptera: Laemophloeidae), the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae), the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) and the psocid, Liposcelis paeta Pearman (Psocoptera: Liposcelididae). The adult insects were exposed to treated grains for 7, 14 and 21 days. For progeny emergence data, the treated units were remained under the same conditions for 62 days for all beetles and 30 days for psocids. The results revealed significant differences in mortalities of insect species among treatments and grains. The combined use of B. bassiana, at the highest dose, and DE increased adult mortalities of all species. In general, the treatments were least effective against T. castaneum and most effective against L. paeta . More numbers of dead insects were found on wheat than on rice or maize. The emergence of progeny was considerably reduced on grains treated with B. bassiana, at the highest dose, plus DE. The results of the present study suggest that the effectiveness of B. bassiana is fortified by the addition of DEs, but it varies among exposed insect species and commodities. Highlights: B. bassiana, at the highest dose, +DE increased mortalities of all species. Treatments were least effective against T. castaneum. Treatments were most effective against L. paeta. More numbers of dead insects were found on wheat than on rice or maize. Progeny was reduced on grains treated with B. bassiana, at the highest dose,  + DE.